Pengaruh Partisipasi Anggaran, Komitmen Organisasi, Teknologi Informasi Terhadap Kinerja Manajerial - Andre Panutan manalu; Shinta Ningtyas Nazar (Jurnal Ekonomi dan Bisnis Digital, 2025)
This study aims to analyze the influence of Budget Participation, Organizational Commitment, Information Technology on Managerial Performance. This study was conducted by analyzing the Managerial Performance of the Protestant Church Youth Movement in Western Indonesia, West Java 2 and Banten. The sample used in this study was 50 Youth Movement administrators using the convenience sampling method. The data used in this study are primary data in the form of questionnaires. The results of the study based on the Budget Participation variable have an influence on the Managerial Performance variable, while the Organizational Commitment and Information Technology variables do not have an influence on the Managerial Performance variable partially. The variables of Budget Participation, Organizational Commitment, Information Technology together have an influence on the Managerial Performance variable.